Efficacy of Adaptation of Smallholder Maize Production to Climate Variability in Selected Countries of Kenya - Kabara, Millicent; Onono-Okelo, Perez Ayieko; Etyang, Martin N. (European Scientific Journal, ESJ, 2023)
Maize is a staple food for 96 percent of Kenyans. Smallholders supply up to 75 percent of maize produced in Kenya but are affected by unpredictable timing, duration, and distribution of rainfall, especially during the growing season. To enhance maize productivity adoption of robust adaptation measures is vital. The study aimed to evaluate the level of efficacy of adaptation of smallholder maize production to climate variability in Kitui and Laikipia counties. Data from 273 smallholder maize producers drawn from Kitui and Laikipia counties was analyzed. A questionnaire was administered to collect data on demographic, socio-economic characteristics, and adaptation choices. The level of efficacy of adaptation was derived based on the Multiple Criteria Evaluation. Results showed that the majority of smallholders in the study (47 percent) reported a low level of efficacy of adaptation most of whom were from Laikipia County (54 percent) as compared to Kitui County (44 percent). Overall, a very small proportion of smallholders reported a high level of efficacy of adaptation (7 percent). The study concluded that the level of efficacy of adaptation of smallholder maize production to climate variability in semi-arid areas was low. The County Governments through the department of agriculture and environment could establish guidelines for a robust combination of adaptation choices to ensure the suitability and enhancement of maize production.